UiTM swimming pool water heating system / Bukhari Manshoor - Manshoor, Bukhari (2003)
The total primary energy demand in Malaysia projected to increase at an annual growth rate of 7% by the year 2020. This growth rate means Malaysian energy industries will be on average 5.4 times larger than that in 1995. The electricity generation, transmission and distribution sector will be six times larger than it will today. Thus, it is necessary to tap alternative renewable energy sources to fulfil the energy demand in the future. To overcome the energy demand in Malaysia, the alternative energy that can be choosen is solar energy. In this project, that is to study and propose the system that can control water temperature for UiTM swimming pool, the authors chose to use a solar water heating system. Beside the using of the solar energy as an alternative energy in water heating system, the author also want to realise this system in UiTM as one of the teaching materials or aids especially for subjects that involve directly in the area of fluid and heat transfer.